1995
DOI: 10.1136/vr.136.19.485
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various levels of T-2 toxin on the clinical status, performance and metabolism of growing pigs

Abstract: In two sets of experiments eight groups of seven-week-old pigs weighing about 9 kg were fed for three weeks a prestarter that contained 0.5, 1.0, 2.0, 3.0, 4.0, 5.0, 10.0 or 15.0 mg/kg of highly purified T-2 toxin. The feed of the two control groups was free from T-2 toxin. Average daily intakes of toxin by the pigs were 0.38, 0.81, 1.24, 1.43, 0.93, 0.81, 0.99 and 2.5 mg, respectively. The weight gains, the feed intakes, the extent of feed refusal, the parameters of energy and protein metabolism and the serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…A similar observation was reported by (Rafai et al, 1995a). Moreover, this reduction in weight gain was the only clinical sign observed; indeed biochemical plasma parameters remained unchanged even after 28 days of exposure.…”
Section: Discussionsupporting
confidence: 85%
“…A similar observation was reported by (Rafai et al, 1995a). Moreover, this reduction in weight gain was the only clinical sign observed; indeed biochemical plasma parameters remained unchanged even after 28 days of exposure.…”
Section: Discussionsupporting
confidence: 85%
“…The use of the pure form, however, may still result in differences in estimates. Thus, Rafai et al (1995a) commented that feed refusal in pigs fed T-2 toxin at 3 mg/kg was a particular problem whereas other earlier studies had indicated no such effects at considerably higher levels of the mycotoxin. The choice of performance and biochemical criteria may also influence selection of tolerance values.…”
Section: Advisory and Tolerance Limitsmentioning
confidence: 80%
“…It is may be significant that other trichothecenes including NIV and T-2 toxin have been implicated in both feed refusal and anorexia in pigs (Table 1). Thus, Rafai et al (1995a) observed dose-related depressions in feed intake within one week of feeding diets contaminated with T-2 toxin. By the end of the 3-week study pigs fed T-2 toxin at 3 mg/kg had feed intakes which were only 0.59 of control values.…”
Section: Jpf D'mello Et Al / Animal Feed Science and Technology 8mentioning
confidence: 98%
See 1 more Smart Citation
“…5,30 According to the literature, some Fusarium toxins may affect the performance of pigs in very low amounts; for example, T-2 toxin induces feed rejection, resulting in reduced body weight gain in a concentration as low as 0.5 mg/kg of feed. 24 On the other hand, FB 1 did not affect feed intake and body weight gain even when fed in much higher concentrations (eg, 40 mg/kg of feed), despite the fact that the pigs ingesting it had developed rather severe pulmonary edema but no obvious clinical signs of pulmonary disease. 38 Another similar experiment conducted with growing pigs showed that dietary exposure from 1 to 10 ppm of FB 1 caused uneven body weight gain in the first 4 weeks of life, but growth stabilized between weeks 4 and 8.…”
Section: Discussionmentioning
confidence: 99%